FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG PERUSAHAAN MANUFAKTUR DI INDONESIA DAN MALAYSIA - Rosmawati Endang Indriyani; Supriyati Supriyati (STIE Perbanas Surabaya, 2012)
The purpose of the research is determining the factors that influence audit report lag inmanufacturing companies in Indonesia and Malaysia from 2009 to 2010. Factors are firmsize, profitability, corporate income and debt to equity ratio. The data used were obtainedfrom Indonesia and Malaysia Stock Exchange. This study used purposive sampling methods.Analysis methods used descriptive analysis, the assumptions of classical test (such as normality,multicolinearity, autocorrelation and heterocedasticity) and multiple linear regressions.The results of multiple linear regression show that audit report lag in Indonesia andMalaysia simultaneously influenced by firm size, profitability, corporate income and debt toequity ratio, audit report lag in Indonesia partially influenced by firm size and debt to equityratio, and in Malaysia audit report lag partially influenced by firm size.